Building Scaffolding for "everyone" in Preschool Education through the Suzuki method: an experimental study - Moreno, Davys (2022)
In Portugal, pre-school education (between the age of three and the age of entry into basic education), is considered the first stage of basic education in the process of lifelong education in which the learning opportunities are based on a set of curricular guidelines. In this context, unfortunately, professionals in Pre-school Education do not have satisfactory training that would allow them to possess skills to develop music or musical expression as proposed in the guidelines. A similar situation was found in pre-school education in Chile, despite the importance given to these areas in the Bases Curriculares de la Educación Parvularia of the Chilean Government. In order to respond to this need, an intervention was carried out in three kindergartens, chosen at random, under the National Board of Kindergartens of the Atacama, Chile. The aim of this study was to improve the skills of the teachers in order to promote the level of musical expression, through the method of Dr. Shinishi Suzuki, for all children, including children with special needs. The study involved the direct participation of 18 Kindergarten teachers and, indirectly, 125 children out of a total of 2126 children. The work was carried out over two school years. In the first year the teachers were subjected to a musical training course in which they learned to play the violin. In the second year they replicated their learning in music for all the children, promoting the inclusion of children with special needs in the classrooms, acting as scaffolding for the development of all the children in their groups of students (experimental group). A comparative experimental quantitative methodology was used with the use of a control group that was not subject to the intervention. The results of the intervention were assessed by blindly applying the standardised Instrumento de Avaliación para el Aprendizaje test to the children belonging to both the experimental and control groups at the beginning and end of the study. It was found that the children in the experimental group, including the children with special needs, significantly improved their skills in the areas of communication and socialisation compared to the children in the control group. We conclude that the training of teachers in music certainly contributes to the improvement of children's skills in communication and socialisation, positively promoting the inclusion of children with special needs in their environment and with their peers.